Lattice Boltzmann simulations of contact line motion. I. Liquid-gas systems - Briant, A; Wagner, A; Yeomans, J (2004)
The applicability of a mesoscale modeling approach to the problem of contact line motion in one and two phase fluids was investigated. The thermodynamics boundary conditions were implemented, which allows to fix the static contact angle in the simulations. It was found that the contact line was overcome by evaporation or condensation near the contact line which was driven by the curvature of the diffuse interface. An analytic approximation was also derived for the angular position of a sheared interface.